Response of Native Chickens (3-10 Weeks) Fed on Diets Substituated With Graded Levels of Sweet Potato Fermentation - Frengki Damu Lodu; Ni Ketut Etty Suwitari; Luh Suariani (SEAS (Sustainable Environment Agricultural Science), 2022)
The purpose of this study was to determine the effect of giving fermented sweet potato waste in the ration on the appearance of native chickens aged 3 - 10 weeks and to find out what percentage of the level of use of fermented sweet potato waste in the ration. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. The treatments consisted of: R0 = ration without additional fermented sweet potato waste as control, R1 = ration containing 3% unfermented sweet potato was, R2 = ration containing 3% fermented sweet potato waste, R3 = ration containing 6% fermented sweet potato waste, R4 = The ration contains 9% fermented sweet potato waste. Each replication (experimental unit) used 5 native chickens so that the number of chickens used was 75. The use of sweet potato waste fermentation in the ration had no significant effect (P>0.05) on initial body weight, final body weight , weight gain,and feed convertion ratio. Feeding of fermented sweet potato waste to a level of 3% (R2) gave optimal results.